ANALYSIS OF THE GRAVITY ANOMALY IN THE GEOTHERMAL PROSPECTIVE REGION - SEKAR ASIH (NIM : 10212041), NIKEN
Geothermal energy is the heat energy that comes from inside the Earth are characterized by their surface manifestations. Geophysical methods has an important role in the exploration stage in the discovery of potential geothermal energy sources, namely to reconstraction dimensions of the anomalies associated in the research area. In this paper geophysical method used is the gravity method with a physical quantity that is obtained is the price of the gravitational acceleration geothermal prospect area. Gravity measured response is different at each point of measurement, it is caused by the gravity anomaly beneath the surface. To see the gravity anomaly is used modeling fore. In this paper carried forward modeling with MATLAB software and the result compared with field data from the measurement. Data field used a complete Bouguer anomaly data is then performed using polynomial separation into regional anomalies and anomaly residual. The results of forward modeling form of the model parameters can be changed in order to obtain the response of gravity with an average density of the study area was 2.84 kg / cm3.